Tuberculous myelopathy associated with longitudinally extensive lesion: a clinicoradiological review of reported cases - Md Noh, Mohamad Syafeeq Faeez; Bahari, Norafida; Abdul Rashid, Anna Misyail (Korean Neurological Association,Daehan Sin-gyeong Gwahaghoe, 2020)
Acute transverse myelitis is an inflammatory disorder of the spinal cord in which there is no evidence of spinal cord compression. Longitudinally extensive transverse myelitis (LETM) is a specific subtype of acute transverse myelitis that usually affects three or more vertebral levels and produces marked neurological deficits. While the most-common cause of LETM is neuromyelitis optica or neuromyelitis optica spectrum disorder, there are rare cases of other causes mimicking this condition, including tuberculosis (TB). We sought to review the clinicoradiological features of TB myelopathy associated with longitudinally extensive lesion, which may mimic LETM, in the English literature. We searched the PubMed, Google Scholar, Web of Science, and Scopus databases for relevant articles using search terms including “longitudinally extensive transverse myelitis,” “tuberculosis,” “TB spinal cord,” and various combinations of these expressions. Full-text papers were selected without limiting the publication year. We also examined the reference lists of key papers to identify further articles that are potentially relevant. We found 10 cases in 7 papers describing TB myelopathy associated with longitudinally extensive lesion. The demographics, clinical features, relevant cerebrospinal fluid findings, and radiological findings were compiled and summarized. TB myelopathy associated with longitudinally extensive lesion is very rare, with no documented prevalence. Early and accurate diagnosis is important since the condition is potentially treatable.